Complementary tasks and the limits to the division of labour - Dennis Görlich (Kiel Institute for the World Economy (IfW), 2010)
During the recent decades, multitasking has become a more and more common phenomenon at workplaces. Rather than specializing in a job task, workers perform bundles of tasks. Bundling occurs when tasks are complements. Using individual-level data about job tasks, we analyze which tasks are complements. Such intrapersonal task complementarities limit the division of labour as complementary tasks can only be unbundled at a cost (productivity loss). To illustrate this point, we apply our findings to the debate about the offshorability of jobs and show that the number of potentially offshorable jobs is significantly lower when task complementarities are accounted for. We also advance the current literature on offshorability by introducing an indicator at the task-level, rather than the occupation-level.
Keywords: F16; L23; J22; 330; Tasks; complementarities; offshoring; offshorability; division of labor; Anforderungsprofil; Arbeitsteilung; Offshoring; Theorie